EARLY RISK ASSESSMENT OF OPPORTUNISTIC INFECTIONS IN HIV-INFECTED CHILDREN USING NEUTROPHIL-TO-LYMPHOCYTE RATIO AND PLATELET-TO-LYMPHOCYTE RATIO - A PROSPECTIVE COHORT ANALYSIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This prospective study evaluates the diagnostic utility of neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio for early opportunistic infection risk stratification in 98 HIV-infected children. Neutrophil-to-lymphocyte ratio above 3.2 demonstrated sensitivity of 88.2% and specificity of 84.6%. Combined index application increased sensitivity to 92.6%, establishing these accessible hemogram-derived biomarkers as reliable, cost-effective early warning instruments in pediatric HIV management.